Knowledge, Attitude and Practice Regarding COVID-19 among Healthcare Workers in Chattogram, Bangladesh - Dutta, Mukesh Kumar; Barua, Bidduth; Rubayat, Rahnuma; Nasreen, Hasina; Biswas, Suman (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: The coronavirus disease 2019 (COVID-19) is a pandemic respiratory disease caused by the highly contagious novel coronavirus (SARS-CoV 2). COVID-19 pandemic continues to challenge healthcare services worldwide. Healthcare Workers (HCWs) are more susceptible to COVID-19 infection than the general population due to frequent contact with infected individuals. This study was aimed to assess the knowledge, attitude and practice among HCWs towards COVID-19 in some COVID dedicated hospitals of Chattogram, Bangladesh. Materials and methods: This descriptive cross-sectional study was conducted at three hospitals (Chittagong Medical College Hospital, Chattogram 250 Bed General Hospital, and Bangladesh Institute of Tropical and Infectious Disease) in Chattogram, from January 2021 to August 2021. The study included 393 HCWs (Physicians and nurses) by a non-probability convenient sampling method. An interview administered questionnaire was used to evaluate their knowledge, attitude and practices regarding COVID-19 and their associations with the participants’ characteristics. Results: Participants were predominantly female (230/393, 58.0%) and physicians (313/393, 77.0%). Almost all had sufficient knowledge (85.8%) and good preventive practice (92.1%) towards COVID-19, however, there was also a rather low level of positive attitude recorded, at 69.0%. Factors associated with KAP were, Knowledge: being a physician and higher education. Attitude: age >40 years, Practice: being a physician. Conclusion: The findings demonstrated sufficient knowledge and good preventive practice towards COVID-19, however, positive attitude was lower. Therefore, it is an identified requirement to continue with additional education and training strategies to offer a positive viewpoint of the pandemic for all HCWs. JCMCTA 2021 ; 32 (2) : 79-84